Clinical and MRI Characteristics of Multiple Sclerosis in Iranian Children and Adolescents: Multiple sclerosis in the Iranian Children and Adolescents - Nasehi, Mohammad Mahdi; Nikkhah, Ali; Saket, Sasan; Rezakhani, Sepideh; Hosseini, Mahya; zahed, ghazal; Alizadeh, Reza; Moosazadeh, Mahmood (Iranian Journal of Child Neurology, 2023)
Objective To determine the clinical and MRI characteristics of multiple sclerosis (MS) in the children and adolescents. Material & Methods In this cross-sectional study, information of 95 MS patients was obtained from the Iranian MS registry. Disease characteristics and imaging data were collected using medical records. Results Ninety-five patients including 64 female and 31 male subjects with mean age of 13.97±2.4 (range, 8-18) years were enrolled. The most frequent signs and symptoms were ophthalmic symptoms (n=61, 64.2%), brainstem signs (n=44, 46.3%), cerebellar signs (n=32, 33.6%) and pyramidal signs (n=26, 27.3%). Blurred vision (n=21, 34.4%) was the most common ophthalmic symptom and ataxia (n=24, 75%) the most prevalent cerebellar sign. The most common brainstem signs/symptoms were motor symptoms and vertigo (each n=14, 31.8%) and the most common pyramidal sign/symptom was right upper monoparesis (n=14, 23.3%). Active demyelinating lesions were reported in brain MRI of all patients, mostly appeared as periventricular (n=91, 95.8%) and pericallosal (n=55, 57.9%) lesions. Acute demyelinating spinal lesions were presented in 38 patients (51.3%) with a prominent involvement of the cervical spine (n=33, 86.8%). Conclusion In our study, the most frequent signs and symptoms were eye symptoms, brainstem signs, cerebellar signs and pyramidal signs, respectively. Moreover, our results showed that MRI plays a critical role in the diagnostic evaluation of MS in children with presence of brain lesions in all patients and spinal lesion in a considerable portion of patients.